2006
DOI: 10.1002/dc.20392
|View full text |Cite
|
Sign up to set email alerts
|

Specimen adequacy and diagnostic specificity of ultrasound-guided fine needle aspirations of nonpalpable thyroid nodules

Abstract: Ultrasound-guided fine needle aspiration (USG-FNA) is a safe, effective, and dependable test used to assess thyroid nodules. However, the size of the lesion can adversely affect the outcome of the procedure. The aim of this study was to assess specimen adequacy and diagnostic specificity in USG-FNA of thyroid nodules measuring < or = 1.5 cm. A total of 219 thyroid FNAs were performed in a one year; 26 were obtained by pathologists, 139 by clinicians, and 54 by radiologists under ultrasound guidance. Of the 54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 12 publications
2
28
0
2
Order By: Relevance
“…Until recently, various diagnostic terminologies, including ‘atypical’, ‘indeterminate’, and ‘suspicious for malignancy’, were used to describe diagnostically challenging cases [26,27]. Furthermore, until recently there were no uniform criteria established for the specimen adequacy [28,29]. This resulted in diagnostic inconsistencies and difficulties in conveying the clinical implications of the thyroid FNA result to the various clinical teams.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, various diagnostic terminologies, including ‘atypical’, ‘indeterminate’, and ‘suspicious for malignancy’, were used to describe diagnostically challenging cases [26,27]. Furthermore, until recently there were no uniform criteria established for the specimen adequacy [28,29]. This resulted in diagnostic inconsistencies and difficulties in conveying the clinical implications of the thyroid FNA result to the various clinical teams.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 1 shows the flow diagram of the results of clinico-pathological correlation of Categories III (A), IV (B), and V (C) by the Bethesda System, which were rela- Further, until recently, there were no uniform criteria established for the various diagnostic categories and specimen adequacy [22,23]. As a result, diagnostic inconsistencies exist among different laboratories as well as pathologists within the same laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…In 2006, Kelly NP et al reported that on ultrasound guided FNA of non palpable thyroid nodules adequate material may be obtained for a specific cytopathological diagnosis and in 17 (89%) cases specific cytological diagnosis was made. 10 In the indeterminate category 4 cases were found to colloid goitre with cystic changes, and three cases were reported as colloid goitre due to adequate material. One midline swelling clinically diagnosed as thyroglossal cyst turned out to be papillary carcinoma on biopsy.…”
Section: Agarwal Et Al Free-hand Versus Usg Guided Fi Ne Needle Aspirmentioning
confidence: 96%